A HYPNOSIS-BASED GROUP INTERVENTION TO IMPROVE QUALITY OF LIFE IN CHILDREN WITH CANCER AND THEIR PARENTS. Issue 2 (3rd April 2019) - Grégoire, Charlotte; Chantrain, Christophe; Faymonville, Marie-Elisabeth; Marini, Jennifer; Bragard, Isabelle
Abstract: Many children with cancer and their parents suffer from distress, fatigue, and relational difficulties. Hypnosis is often used to decrease children's procedure-related pain and distress in pediatric oncology and to improve the well-being of adults with cancer. This article describes a pilot study assessing the acceptability and feasibility of a group intervention combining self-care and hypnosis for children with cancer and their parents, and a quasi-experimental protocol aimed at assessing the efficacy of this intervention to improve quality of life, distress, fatigue, and coping. The pilot study showed that the intervention was feasible and perceived positively. Future research is needed to test the efficacy of group interventions combining self-care and hypnosis to improve quality of life for children with cancer and their families.